"You're naked, you're vulnerable": Sexual well-being and body image of women with lower limb lymphedema. (September 2016) - Winch, Caleb J.; Sherman, Kerry A.; Smith, Katriona M.; Koelmeyer, Louise A.; Mackie, Helen; Boyages, John
Highlights: We explored sexual well-being in women with lower-limb lymphedema. Negative body image was central to women's sexual concerns. Body image was connected with themes including partner support and coping style. Most women interviewed said physical sexual function was not meaningfully affected. Abstract: Lower-limb lymphedema is an incurable illness manifesting as visible swelling enlarging the leg(s) and/or feet, buttocks, and genitals. This study used semi-structured interviews and thematic analysis to explore sexual well-being among women with primary (congenital) lymphedema ( n  = 11) or secondary lymphedema associated with gynecological cancer ( n  = 8). Five themes (subthemes) summarized women's responses, with Attractiveness and Confidence (Publicly Unattractive, Privately Unconfident, Lymphedema or Aging?) describing women's central concern. These body image-related concerns accounted for sexual well-being in association with Partner Support (Availability of Support, Languages of Support, Fears About Support) and the degree of Functional Interruptions (Lymphedema in Context, Enduring Impacts, Overcoming Interruptions). Successful Lymphedema Coping (Control, Acceptance) and self-perceived ability to fulfill a valued Sexual Role also affected sexual well-being. Few differences between women with primary versus secondary lymphedema were evident. Lymphedema clinicians should screen for sexual concerns and have referral options available.